2002
DOI: 10.1111/j.1559-1816.2002.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Body Comparison Among Adolescent Girls1

Abstract: Grade differences in appearance and nonappearance social comparisons, and targets for body comparison were examined in adolescent girls. A model describing potential contributors to, and consequences of, body comparison tendency was examined. Girls (n= 545) completed measuring social comparisons, targets for comparisons, dieting in response to comparisons, body attitudes, eating patterns, psychological variables, height, and weight. Appearance and nonappearance social comparisons increased with age. Girls repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
2
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 68 publications
7
118
2
12
Order By: Relevance
“…Some research examining the impact of appearance comparisons to these different target groups has shown that comparisons to peers and models can lead to different outcomes in regard to women's body image concerns, perhaps because the appearance of peers is seen to be more personally attainable than the appearance of models or celebrities due to the similar resources and lifestyle that peers often have to oneself. However, the findings in the area are mixed (Carey, Donaghue, & Broderick, 2013;Leahey & Crowther, 2008;Ridolfi, Myers, Crowther, & Ciesla, 2011;Schutz, Paxton, & Wertheim, 2002), and a meta-analysis of research on appearance comparisons and body dissatisfaction found no significant difference between the effects of comparisons to peers or thinideal media images on women's body dissatisfaction (Myers & Crowther, 2009). …”
Section: Comparison Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research examining the impact of appearance comparisons to these different target groups has shown that comparisons to peers and models can lead to different outcomes in regard to women's body image concerns, perhaps because the appearance of peers is seen to be more personally attainable than the appearance of models or celebrities due to the similar resources and lifestyle that peers often have to oneself. However, the findings in the area are mixed (Carey, Donaghue, & Broderick, 2013;Leahey & Crowther, 2008;Ridolfi, Myers, Crowther, & Ciesla, 2011;Schutz, Paxton, & Wertheim, 2002), and a meta-analysis of research on appearance comparisons and body dissatisfaction found no significant difference between the effects of comparisons to peers or thinideal media images on women's body dissatisfaction (Myers & Crowther, 2009). …”
Section: Comparison Targetsmentioning
confidence: 99%
“…Similarly, we hypothesized that exposure to an online fashion magazine would lead to more negative mood, body dissatisfaction, weight and shape discrepancy, and face, hair, and skin-related discrepancy than would exposure to an appearance-neutral control website. Given that no previous research has examined the difference between exposure to Facebook vs. a magazine (online or in print), and given that previous research on comparisons to peers and models is mixed (Carey et al, 2013;Leahey & Crowther, 2008;Ridolfi et al, 2011;Schutz et al, 2002), no specific hypotheses were made regarding Facebook vs. the online fashion magazine. Finally, appearance comparison tendency was predicted to moderate the relationship between exposure to an assigned website (Facebook, online fashion magazine, control) and state negative mood, body dissatisfaction, and appearance discrepancies.…”
Section: The Present Studymentioning
confidence: 99%
“…Friends' concern with thinness was assessed using 12 questions adapted from Paxton and colleagues (Paxton et al 1999) and Schutz and colleagues (Schutz et al 2002; see Table 2). These items were rated on a 5-point scale, with higher scores indicating greater perceived peer concern.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Another study showed that body comparison was positively related to restraint and a tendency to diet, among adolescent girls. 23 Similarly, among women serious dieting and disordered eating are strongly related to competitive- ness. In creating their measure of dieting-related competitiveness, Huon et al, 24 found that adolescent girls who were the most serious dieters and most dissatisfied with their bodies had the highest competitiveness scores.…”
Section: Discussionmentioning
confidence: 99%